Pengaruh Model Pembelajaran Berbasis Proyek terhadap Pengetahuan Prosedural Siswa pada Konsep Eubacteria - Nengsih Juanengsih; Leilyana Purnamasari; Buchori Muslim (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2017)
This study aims to determine the effect of project-based learning model to the students' procedural knowledge on the concept of eubacteria. This research was conducted during October 2015 in one of State Senior High School in Jakarta. The research method used is Quasi-Experiments. The research sampling technique used simple random sampling, with sample of 30 students for experimental group and 30 students for control group. The instrument used in this research is 10 procedural knowledge description test. Based on the data analysis through t-test statistic, the results indicate that there is an influence of project-based learning model to the students' procedural knowledge on the concept of eubacteria.